2022
DOI: 10.1016/j.jhin.2022.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Effective ultraviolet C light disinfection of respirators demonstrated in challenges with Geobacillus stearothermophilus spores and SARS-CoV-2 virus

Abstract: Background The global Covid-19 pandemic accompanied by spikes in the number of patients in hospitals, required substantial amounts of respiratory protective devices (respirators) thereby causing shortages. Disinfection of used respirators by applying UVC light may enable safe reuse, reducing shortages. Here, UVC light is explored for disinfection of respirators. Aim To determine whether UVC disinfection is applicable to enable repeated safe reuse of respirators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…When the dose of UVC is 10 J/cm 2 , UVC can contact with viruses and microorganisms in all parts of the mask, and make their reduction of >5 log10 (The J/cm 2 is widely used in decontamination literature to show UVC flux). At doses up to 6 times higher than the standard dose, the respirator fitting integrity and filtration capacity would not be significantly affected [75] . Studies have shown that the ideal dose of some N95 FFRs is 1.5J/cm 2 [29] .…”
Section: Decontamination and Reuse Of Masksmentioning
confidence: 97%
“…When the dose of UVC is 10 J/cm 2 , UVC can contact with viruses and microorganisms in all parts of the mask, and make their reduction of >5 log10 (The J/cm 2 is widely used in decontamination literature to show UVC flux). At doses up to 6 times higher than the standard dose, the respirator fitting integrity and filtration capacity would not be significantly affected [75] . Studies have shown that the ideal dose of some N95 FFRs is 1.5J/cm 2 [29] .…”
Section: Decontamination and Reuse Of Masksmentioning
confidence: 97%
“…Conventionally, UV-C sources at 254 nm are used for the disinfection of surfaces 13 , instruments 14 or room air 15 , 16 in shielded air cleaners that prevent human exposure. This is crucial, as UV-C radiation at 254 nm is highly cytotoxic, reduces cell viability 17 and causes a large amount of DNA damage.…”
Section: Introductionmentioning
confidence: 99%